Preface to the Special Issue of Initial Scientific Results of MSS-1 - Keke Zhang; PengFei Liu; YongXin Pan (Earth and Planetary Physics)
The scientific research of geomagnetism has been largely driven by new geomagnetic data that are available to scientists. Macau Science Satellite-1 (MSS-1) was successfully launched on 21st May 2023 into a near-circular orbit of altitude of about 450 km with a low inclination of 41°. After careful evaluation and calibration (7th June 2023 to 31st July 2024), the data of MSS-1 were released to the international scientific community on 1 August 2024, providing the highly accurate data of global geomagnetic field with an unprecedented local-time coverage to the community. This special issue of Initial Scientific Results of MSS-1, primarily driven by the new MSS-1 data, contains 27 research articles ranging from the MSS-1 design, satellite data analysis, outer core dynamics, mantle induction, lithospheric field modeling, ocean induced magnetic field, ionosphere and magnetosphere currents, to solar activities.